2017
DOI: 10.1103/physrevx.7.011030
|View full text |Cite
|
Sign up to set email alerts
|

Strong Coupling Cavity QED with Gate-Defined Double Quantum Dots Enabled by a High Impedance Resonator

Abstract: The strong coupling limit of cavity quantum electrodynamics (QED) implies the capability of a matter-like quantum system to coherently transform an individual excitation into a single photon within a resonant structure. This not only enables essential processes required for quantum information processing but also allows for fundamental studies of matter-light interaction. In this work we demonstrate strong coupling between the charge degree of freedom in a gate-defined GaAs double quantum dot (DQD) and a frequ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
312
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 265 publications
(321 citation statements)
references
References 35 publications
7
312
0
2
Order By: Relevance
“…b. Strong coupling limit Very recently, the strong coupling regime was reached simultaneously in three experiments based on different types of charge double quantum dots [30][31][32] . In this regime, for a low number of photons ñ → 0, the cavity transmission (or reflection) amplitude versus the frequency excitation ω RF shows a double peak, due to the strong hybridization between the cavity and the L/R charge degree of freedom of the double dot (see Fig.9d).…”
Section: Resultsmentioning
confidence: 99%
“…b. Strong coupling limit Very recently, the strong coupling regime was reached simultaneously in three experiments based on different types of charge double quantum dots [30][31][32] . In this regime, for a low number of photons ñ → 0, the cavity transmission (or reflection) amplitude versus the frequency excitation ω RF shows a double peak, due to the strong hybridization between the cavity and the L/R charge degree of freedom of the double dot (see Fig.9d).…”
Section: Resultsmentioning
confidence: 99%
“…Recent experiments on such systems, using conductors such as Josephson junction (JJ) devices [1][2][3], or quantum dots [4,5], have demonstrated that coherent interactions between a conductor and a cavity can generate large non-equilibrium photon populations. Parallels can be drawn between cavity-conductor hybrids and quantum optical devices such as the micromaser in which a stream of excited atoms flows through an optical cavity [6,7]; in both cases the photons in the cavity act back on the photon generation process leading to strongly nonlinear dynamics and dissipative phase transitions.…”
Section: Introductionmentioning
confidence: 99%
“…Using a high-impedance Z 0 considerably increases coupling rates compared to typical 50 implementations by increasing the voltage zero-point fluctuations of the cavity V zpf ∝ √ Z 0 as exploited in cavity QED with quantum dots [19]. When the transmon and fundamental mode of the cavity are resonant, we spectroscopically measure a coupling g/2π = 455 MHz, corresponding toḡ = 0.071.…”
Section: Introductionmentioning
confidence: 99%